(3JYdjb GdaQGFO Ydi JSgjd GdahGFOs - (3eMeO Hf CHj HcQ Hf YeQ Hf CHj HcQ Hf eMeO, GdeNRhej GdbQTj, HOQ GdOjf GdeYQha HGHf GdOeGejfj , J (B827 (3g` s; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3CeG HYO, adG jNai Cf GdcJGH GdeSei HJSgjd GdahGFO hJcejd GdebGUO, JCdja HGf eGdc s
(3BNQgG (B:s
(3aGdYed ddeUOQ hGeJfY GdJbOje GfJgi GdfUa GdChd s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjI JJab aj ChdgG eY Chd GdfSNI GdChdi HGNJdGa aj HYV GdCdaGXs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B130s
Keywords: (3GdfMhs